The Influence of Principal’s Strategy and Work Climate on Teacher Professionalism at SMP Katolik Gonzaga Tomohon - Rahel Gabriela Lolong; Jefry Sony Junus Lengkong; Zoya Febrina Sumampouw (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of the principal's strategy and work climate, both partially and simultaneously, on teacher professionalism at SMP Katolik Gonzaga Tomohon. Using a quantitative associative approach with an ex-post facto design, this research involved the entire teacher population of 40 individuals as respondents through a total sampling technique. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability and were analyzed using multiple linear regression. The results showed that: (1) The principal's strategy has a positive and significant effect on teacher professionalism (t=3.626; p<0.001) and is the most dominant variable; (2) The work climate has a positive and significant effect on teacher professionalism (t=2.637; p=0.012); and (3) Simultaneously, the principal's strategy and work climate have a significant effect on teacher professionalism, contributing 74.9% (=0.749). These findings confirm that improving teacher professionalism at SMP Katolik Gonzaga Tomohon heavily depends on the synergy between planned managerial policies and the creation of a conducive working atmosphere.